Katzung & Trevor's pharmacology : examination & board review - Bertram G. Katzung; Marieke Kruidering-Hall; Anthony J. Trevor (New York : McGraw Hill Education, 2019)
"This book is designed to help students review pharmacology and to prepare for both regular course examinations and board examinations. The twelfth edition has been revised to make such preparation as active and efficient as possible. As with earlier editions, rigorous standards of accuracy and currency have been maintained in keeping with the book's status as the companion to the Basic & Clinical Pharmacology textbook."
Keywords: Examination Questions; Pharmacology Examinations, questions, etc